2010
DOI: 10.1371/journal.pone.0011479
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Chikungunya Virus into Mammalian Cells: Role of Clathrin and Early Endosomal Compartments

Abstract: BackgroundThe replicative cycle of chikungunya virus (CHIKV), an alphavirus that recently re-emerged in India and in Indian Ocean area, remains mostly unknown. The aim of the present study was to investigate the intracellular trafficking pathway(s) hijacked by CHIKV to enter mammalian cells.Methodology/Principal FindingsEntry pathways were investigated using a variety of pharmacological inhibitors or overexpression of dominant negative forms of proteins perturbating cellular endocytosis. We found that CHIKV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
169
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(181 citation statements)
references
References 56 publications
11
169
0
1
Order By: Relevance
“…4 The ribbon image showing superimposition of the modeled E2 protein (purple color) and the crystallized immature E1-E2-E3complex of Chikungunya virus [46] (PDB Id: 3n40) (green color) (color figure online) by Hunt and colleagues reported that Bafilomycin A1 was found to block the expression of a virus-encoded reporter gene of sindbis virus in both infection and transfection of the BHK cells [18]. Further, another study reported limited inhibitory effect of bafilomycin in post CHIKV infection in HEK239T cells [5]. The inhibitory effect of bafilomycin has also been reported previously for other viruses like influenza [17].…”
Section: Molecular Docking and MD Simulation Studiesmentioning
confidence: 99%
“…4 The ribbon image showing superimposition of the modeled E2 protein (purple color) and the crystallized immature E1-E2-E3complex of Chikungunya virus [46] (PDB Id: 3n40) (green color) (color figure online) by Hunt and colleagues reported that Bafilomycin A1 was found to block the expression of a virus-encoded reporter gene of sindbis virus in both infection and transfection of the BHK cells [18]. Further, another study reported limited inhibitory effect of bafilomycin in post CHIKV infection in HEK239T cells [5]. The inhibitory effect of bafilomycin has also been reported previously for other viruses like influenza [17].…”
Section: Molecular Docking and MD Simulation Studiesmentioning
confidence: 99%
“…A detailed entry mechanism description is not available so far. Some authors implicate a clathrin-dependent pathway [64,66], whereas other authors have proposed that CHIKV enters by a clathrin-independent, but Eps15-dependent pathway [65]. These later authors also have found evidence that multiple pathways maybe employed by CHIKV to enter into cells, as already proposed with dengue virus (DENV) [67,68].…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 95%
“…Viral replication is initiated by attachment of viral envelope to host cell receptors [63], followed by low pH-mediated membrane fusion and delivery of the viral nucleocapsid into the cytoplasm (Fig. 1) [64,65]. A detailed entry mechanism description is not available so far.…”
Section: Genomic Organization and Viral Replicationmentioning
confidence: 99%
“…Although specific host receptors for CHIKV are still to be determined, CHIKV is believed to enter cells by receptor-mediated pathway through E2 glycoprotein (Weber et al, 2017) (Figure 4B), and it is internalized either via clathrin-mediated endocytosis or a clathrin-independent Eps-15-dependent endocytosis pathway (Hoornweg et al, 2016), like other alphaviruses. Eps-15 is a member of clathrin-coated pits (Bernard et al, 2010). With the progress of infection, the endosome become acidic, inducing the dissociation of E2-E1 heterodimer and a conformation change of E1 membrane fusion protein, allowing host cell membrane and virus envelop to fuse, followed by the release of viral nucleocapsids into the cytoplasm (Gibbons et al, 2004;Bernard et al, 2010).…”
Section: Virus Life Cyclementioning
confidence: 99%
“…Eps-15 is a member of clathrin-coated pits (Bernard et al, 2010). With the progress of infection, the endosome become acidic, inducing the dissociation of E2-E1 heterodimer and a conformation change of E1 membrane fusion protein, allowing host cell membrane and virus envelop to fuse, followed by the release of viral nucleocapsids into the cytoplasm (Gibbons et al, 2004;Bernard et al, 2010). The nucleocapsid protein will then bind to the ribosome (considered to be cellular uncoating factor) to initiate uncoating, resulting in the release of genomic RNA into the cytoplasm (Singh and Helenius, 1992).…”
Section: Virus Life Cyclementioning
confidence: 99%